Valores pessoais, benefícios e atributos do ato de presentear com chocolate - Sato, Claudia Cristina Macceo (2014)
Gift giving is an ancient and complex behavior, and it holds different meanings which are related to the intentions of the giver, the relationship between those involved in the exchange, and to social issues, enabling the present to be a mean for transmitting different symbolisms. In this work, the act of gift giving was approached by investigating the relationships associated among attributes, benefits and personal values through the act of giving chocolate to someone as a present. The choice for investigating when chocolate products are used forgiving someone a present was due to the frequency of the use of chocolate as a gift. This research, which is of a qualitative approach, was developed through the means-end chain and had laddering as the technique of data collection. Twenty-nine interviews were realized and analyzed through the content analysis technique, which allowed the generation of the implication Matrix as well as the map of hierarchical value. The results showed that the act of giving someone chocolate as a present is analyzed by the consumer through criteria such as who the present will be given to, occasions for handing in a present, comparison to other products and the possibility of shaping meaning. The attributes related to chocolate when thought to be given as a presente were: Price, visuals, variety, brand-name, be found in several retail outlets, be appreciated by most, sensory characteristics and quality. The benefits were: Economy, making the purchase in short periods of time, possibility of buying more or to more people, no harm to health, drawing attention, showing that the other person is special, making the other person happy, minimizing possibility of a mistake, being reminded by the present, maintaining social relationships, demonstrating familiarity of the other, surprising, status/causing a good impression, avoiding routine, getting close to the present receiver, putting oneself in the present, childhood memories, creating good moments, transmitting meaning. And the values identified were: being able, willingness, being close to others, happiness, social recognition, hedonism and prosperous life.